Interiority of Agraharam: Traditional Houses in Temple Towns of India - Singal, Manan (UI Scholars Hub, 2022)
The article aims to provide a multisensory reading within the multiple scales of spaces in the traditional settlement of agraharam. This multisensory reading generates layers of interiority that exist across temples, streets, and houses. Agraharam is the traditional house of the Brahmin (priest) community found in temple towns of South India. This house responds to religious beliefs, tradition, and local climatic conditions and displays a balance of sensory experiences which enrich the overall living experience. In this article, interiority is referred to as the characteristic of being ‘inward,’ where memories and practices of a specific community are associated with the spaces. It explores one's experiences of the various scales (the town, the street, and the house) of spaces through copious physical and sensory experiences, using Pallasmaa’s description of the phenomenological approach to identify the multisensory experience of the human body in space.